2008
DOI: 10.1148/radiol.2462070536
|View full text |Cite
|
Sign up to set email alerts
|

US Imaging of Tumor Angiogenesis with Microbubbles Targeted to Vascular Endothelial Growth Factor Receptor Type 2 in Mice

Abstract: Purpose-To prospectively evaluate contrast material-enhanced ultrasonography (US) with microbubbles targeted to vascular endothelial growth factor receptor type 2 (VEGFR2) for imaging tumor angiogenesis in two murine tumor models. Materials and Methods-Animal protocols were approved by the Institutional Administrative Panel on Laboratory Animal Care. A US contrast agent, consisting of encapsulated gaseous microbubbles, was developed specifically to bind to VEGFR2 (by using anti-VEGFR2 antibodies and biotin-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
249
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(253 citation statements)
references
References 23 publications
4
249
0
Order By: Relevance
“…Ultrasound contrast agents containing encapsulated microbubbles are mainly used to increase the diagnostic imaging of tumors. McCarville et al [18] showed that gray-scale US measurements of microbubble contrast agent flow can be used to detect the functional consequences of antiangiogenic therapy for tumors and to assess angiogenesis inhibitors that act through different mechanisms [19][20][21][22][23] . Recently, lymphangiogenesis has become a new research frontier [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound contrast agents containing encapsulated microbubbles are mainly used to increase the diagnostic imaging of tumors. McCarville et al [18] showed that gray-scale US measurements of microbubble contrast agent flow can be used to detect the functional consequences of antiangiogenic therapy for tumors and to assess angiogenesis inhibitors that act through different mechanisms [19][20][21][22][23] . Recently, lymphangiogenesis has become a new research frontier [10] .…”
Section: Discussionmentioning
confidence: 99%
“…low background in circulation), are optimal. VEGF-R2-targeted microbubbles (MB) are a clinically relevant example of this, and are currently in early-stage trials for prostate cancer staging and treatment monitoring using ultrasound imaging [47,48].…”
Section: Diagnostic Nanomedicinementioning
confidence: 99%
“…In 2 murine tumor models, microbubbles conjugated to anti-VEGFR-2 monoclonal antibodies were used to image VEGFR-2 expression (Willmann, Paulmurugan et al 2008). The targeted microbubbles produced a significantly higher average signal intensity than control microbubbles, and the signal intensity was significantly lower when anti-VEGFR-2 antibodies (blocking antibodies) were used, demonstrating target specificity.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%